O papel dos receptores 5-HT3 da amídala na modulação da ansiedade em camundongos expostos ao labirinto em cruz elevado - Laine, Letícia (Universidade Federal de São Carlos, 2010)
Aversive situations may activate the serotonergic system, which, in turn, emit projections to structures involved in the defense mechanisms such as: septum, hypothalamus, hippocampus, periaqueductal gray and amygdala, producing behavioral alterations that can be characterized as anxiety. Various studies have related the 5-HT3 receptor functions to anxiety-like behaviors. However, serotonin (5-HT) presents a dual role in this modulation. The elevated plus-maze (EPM), based on the rodents natural aversion to open spaces, is one of the most widely employed models used to study anxiety in rodents. Thus, this study investigates the effects of an agonist and an antagonist of 5-HT3 receptors, mCPBG and ondansetron, respectively, on mice exposed to the EPM. Conventional anxiety measures (percentage of open arms entries and percentage of open arms time), locomotor activity (frequency of closed arms entries) and ethological measures related to the risk assessment were registered. The results demonstrated that, in experiments 1 and 2, the intra-amygdala injections of ondansetron (0.3, 1.0 and 3.0 nmol/0.1Ql) and mCPBG (10 and 20 nmol/0.1Ql), produced a decrease and increase, respectively, of the indices of anxiety in mice evaluated on the EPM. In experiment 3, the local ondansetron injection (0.03 nmol/0.1Ql), was able of reverting the anxiogenic effect caused by the mCPBG (10 nmol/0.1Ql). Taken together, these results suggest that the modulation of the 5-HT3 amygdala receptors for the 5-HT receptors in mice, may display an anxiogenic role.
Keywords: Farmacologia; Ansiedade; Serotonina; Ondansetron; mCPBG; Amídala; Labirinto em cruz elevado; Serotonin; Ondansetron; mCPBG; Amygdala; Elevated plus-maze; Mice; CIENCIAS BIOLOGICAS::FISIOLOGIA